Personality Development Beyond the Mean: Do Life Events Shape Personality Variability, Structure, and Ipsative Continuity?. (16th July 2020) - Jackson, Joshua J; Beck, Emorie D
Abstract: Objectives: Life experiences are thought to prompt changes in personality. However, existing studies find few replicable mean-level changes in personality following life events. The focus on mean-level change may obscure other types of personality change that are not routinely studied in the context of life events. These are variability in response, structural, and ipsative change. Methods: The current proposal examines whether major life events (e.g., divorce and job loss) affect these 3 understudied types of personality trait change using 3 waves of Big Five trait data in a large-scale, representative longitudinal study (German Socioeconomic Panel Study, N = 16, 368). Structural equation models compare those who had an event to their prior self and a control group who did not experience the event. Results: Life events were found to have mostly null or small effects on variability in response, structural, and ipsative change. Across 2 types of tests for variability in response, few replications occurred. The only consistent effect across 3 types of change was for mental health events, which served to increase variance in all Big Five traits and increase consistency in ipsative profiles. Discussion: Life events tend not to affect these novel metrics of personality trait change. The one exception of mental health events is consistent with previous literature on mean-level change. Overall, life events do not appear to by major catalysts of personality change, regardless of how change is defined.